An Assessment of the Multifunctionality of Integrated Buffer Zones in Northwestern Europe. Issue 2 (1st March 2019) - Zak, Dominik; Stutter, Marc; Jensen, Henning S.; Egemose, Sara; Carstensen, Mette V.; Audet, Joachim; Strand, John A.; Feuerbach, Peter; Hoffmann, Carl C.; Christen, Benjamin; Hille, Sandra; Knudsen, Mads; et al.
Abstract : Integrated buffer zones (IBZs) have recently been introduced in the Northwestern Europe temperate zone to improve delivery of ecosystem services compared with the services associated with long‐established vegetated buffer zones. A common feature of all the studied IBZ sites is that tile drainage, which previously discharged directly into the streams, is now intercepted within the IBZ. Specifically, the design of IBZs combines a pond, where soil particles present in drain water or surface runoff can be deposited, and a planted subsurface flow infiltration zone. Together, these two components should provide an optimum environment for microbial processes and plant uptake of nutrients. Nutrient reduction capacities, biodiversity enhancement, and biomass production functions were assessed with different emphasis across 11 IBZ sites located in Denmark, Great Britain, and Sweden. Despite the small size of the buffer zones (250–800 m 2 ) and thus the small proportion of the drained catchment (mostly <1%), these studies cumulatively suggest that IBZs are effective enhancements to traditional buffer zones, as they (i) reduce total N and P loads to small streams and rivers, (ii) act as valuable improved habitats for aquatic and amphibian species, and (iii) offer economic benefits by producing fast‐growing wetland plant biomass. Based on our assessment of the pilot sites, guidance is provided on the implementation and management of IBZs within agricultural landscapes. Core Ideas: Integrated buffer zones are a novel edge‐of‐field approach within riparian zones. Drain water and surface runoff will be trapped within a pond and charge a filter bed. The inclusion of trees aims to provide some of the benefits of riparian forests.